1980
DOI: 10.1002/ajim.4700010211
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome investigations in lymphocytes of workers employed in areas in which styrene‐containing unsaturated polyester resins are manufactured

Abstract: Cytogenetic evaluation of 24 employees exposed to an average styrene concentration rate of 6.0 ppm in the laboratory, and to 58.1 ppm in the polyester processing pilot plant, has revealed no statistically significant increase in chromosome aberration rates as compared to a matched control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…So it is somewhat unclear whether the expression "including gaps" of Thiess et a1 119801 should be read as "gaps." This interpretation is suggested by the control result of pair 479 (In Table I of Thiess et al [1980]) where the percentage of aberrant cells including gaps is lower than that excluding gaps. Then, the number of cells with aberrations including gaps would be reached by summarizing the "including gaps" and "excluding gaps" groups of Thiess et al [1980], which yields 5.3% for the control group and 7.0% for the exposed.…”
Section: Comments On the Study Of Thjess And Co-workersmentioning
confidence: 87%
See 1 more Smart Citation
“…So it is somewhat unclear whether the expression "including gaps" of Thiess et a1 119801 should be read as "gaps." This interpretation is suggested by the control result of pair 479 (In Table I of Thiess et al [1980]) where the percentage of aberrant cells including gaps is lower than that excluding gaps. Then, the number of cells with aberrations including gaps would be reached by summarizing the "including gaps" and "excluding gaps" groups of Thiess et al [1980], which yields 5.3% for the control group and 7.0% for the exposed.…”
Section: Comments On the Study Of Thjess And Co-workersmentioning
confidence: 87%
“…In a recent issue of this journal Thiess et al [1980] presented a study of structural chromosome aberrations in the lymphocytes of workers exposed to styrene in a plant manufacturing unsaturated polyester resins. The authors concluded that the study gave no indication that exposure to styrene, at the level encountered, produces cytogenetic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies previously reported that structural chromosomal aberrations in cultured lymphocytes were significantly more frequent in styrene-exposed workers [Meretoja et al, 1977[Meretoja et al, , 1978Fleig and Thiess, 1978;Hogstedt et al, 1979;Sorsa et al, 1979;Anderson et al, 1980;Camurri et al, 1982;Thiess et al, 1980, 19821. However, other data indicated no such increase Thiess and Fleig, 1978;grim, 1981;Watanabe et al, 1981;BrBgger, 19821. Perusal of such reports suggested a possible dose dependency in the effect so that the effects are positive only when the exposure is above a certain critical intensity [Watanabe et al, 19811.…”
Section: Methodsmentioning
confidence: 92%
“…to styrene [BardodEj, 1978;Meretoja et al, 1977Meretoja et al, , 1978bFleig and Thiess, 1978;Thiess and Fleig, 1978;Hogstedt et al, 1979;Sorsa et al, 1979;Husgafiel-Pursiainen et al, 1980;Anderson et al, 19801 and cigarette smoking (see Table 111) have been described in relation to possible increases of chromosome aberrations and sister chromatid exchanges (SCE). However, the results are controversial because some studies demonstrate positive correlations, whereas others result in negative ones.…”
Section: Introductionmentioning
confidence: 99%